(2 Z )-3-Hydroxy-1-(pyridin-2-yl)-3-(pyridin-3-yl)prop-2-en-1one: crystal structure and Hirshfeld surface analysis - Lee, Sze Ling *; Tan, Ai Ling; Young, David J.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The title compound, C13H10N2O2 [also called 1-(pyridin-2-yl)-3-(pyridin-3-yl)propane-1,3-dione], features an almost planar (r.m.s. deviation = 0.0095 Å) central C3O2 core consolidated by an intramolecular hydroxy-O-H...O(carbonyl) hydrogen bond. Twists are evident in the molecule, as seen in the dihedral angles between the central core and the 2- and pyridin-3-yl rings of 8.91 (7) and 15.88 (6)°, respectively. The conformation about the C=C bond [1.3931 (17) Å] is Z, and the N atoms lie to the same side of the molecule. In the molecular packing, supramolecular chains along the a axis are mediated by [pi](pyridin-2-yl)-[pi](pyridin-3-yl) interactions [inter-centroid distance = 3.7662 (9) Å]. The observation that chains pack with no directional interactions between them is consistent with the calculated electrostatic potential, which indicates that repulsive interactions dominate.